A functional proteomic study of the trypanosoma brucei nuclear pore complex: an informatic strategy - DeGrasse, Jeffrey A.; Devos, Damien (Computational Biology, 2010)
The nuclear pore complex (NPC) is the sole mediator of transport between the nucleus and the cytoplasm. The NPC is composed of about 30 distinct proteins, termed nucleoporins or nups. The yeast (Rout et al., J Cell Biol 148:635-651, 2000) and mammalian (Cronshaw et al., J Cell Biol 158:915-927, 2002) NPC have been extensively studied. However, the two species are relatively closely related. Thus, to reveal details about NPC evolution, we chose to characterize the NPC of a distantly related organism, Trypanosoma brucei. We took a subcellular proteomic approach and used several complementary strategies to identify 865 proteins associated with the nuclear envelope. Over 50% of ∼8,100 open reading frames of T. brucei have little or no known function because T. brucei is distantly related to model metazoa and fungi (Berriman et al., Science 309:416-422, 2005). By sequence similarity alone, we could identify only five nucleoporins. This chapter outlines our strategy to identify 17 additional nucleoporins as well as contribute functional annotation data to the T. brucei genome database.